Quality Analysis of Liquid Soap Formulation Made from Virgin Coconut Oil with Addition of White Tea Extract - Meizalin, Anna Amelia; Paramita, Vita (Journal of Vocational Studies on Applied Research, 2021)
The production of bath soap based on natural ingredients is still rarely found in the market. Many in circulation still use synthetic materials as active ingredients. In this soap-making formulation using natural antioxidants in the form of white tea extract, anti-oxidants from plant extracts are usually added as additives (1-8% of the final soap composition). The research method used is a response surface methodology with a Central Composite Design (CCD) design. The resulting liquid soap product will be analyzed including physicochemical tests and organoleptic tests. Soap with the most appropriate quality according to SNI fell on the 4th variable, with the addition of KOH of 67 grams and a reaction time of 35 minutes. Variable soap 4 has a pH of 10, a free alkali content of 0.0541%, and an unsaponifiable fat content of 0.37%.